Succinct scheme of DCT coefficient selection towards enhanced security of JPEG image steganography - Kang WANG; Bei-bei LIU; Shuo-wei LIU; Yong-jian HU (网络与信息安全学报)
Based on the characteristics of JPEG compression,a succinct and effective scheme of DCT coefficients selection was proposed,in which not only the non-zero AC coefficients but also part of the zero coefficients were exploited.Moreover,the scheme embedded messages in a different order than the conventional practice and gave priority to the low frequency coefficients so as to achieve enhanced security.The embedding manners of two typical steganographic algorithms(EPES and APPM)were extended from the spatial to the compression domain and the proposed scheme was applied to them for coefficient selection and embedding.Experimental results showed that larger capacity and better security were achieved compare to three classical steganographic algorithms(JSteg,F5 and nsF5)and one current steganographic algorithm based on STC framework(LPD).The proposed coefficient se-lection and embedding scheme can effectively improved the performance of some classic DCT domain steg-anographic methods in terms of capacity and security.The scheme was general and could be easily applied to dif-ferent steganography methods.